DETECÇÃO DO GENE mecA EM ESTAFILOCOCOS COAGULASE NEGATIVA RESISTENTES A OXACILINA ISOLADOS DA SALIVA DE PROFISSIONAIS DA SAÚDE DE UM HOSPITAL UNIVERSITÁRIO - ROSA, Juliana de Oliveira (2008)
Coagulase negative staphylococci (CNS) is in human and animal microbiota, but may cause with infections with significant morbidity and mortality rates. Healthy care workers may be carriers of many microorganisms and spread resistant ECN in the hospital. This study aimed to identify the CNS species isolated from healthy care workers saliva, establishe the oxacillin resistance pattern and detect the mecA gene in resistant isolates. We evaluated 100 ECN, isolated from the saliva of an institution of professional health of large Riberão Preto in Sao Paulo state. The ECN identification was based on biochemical tests, and 41 were identified as S. epidermidis, 25 S. saprophyticus, 18 S. haemolyticus, 8 S. cohnii, 4 S. lugdunenses, 3 S. capitis, and 1 S. simulans. Thirty-two percent were nonsusseptible to oxacillin, 84.4% to mupirocin, 43.7% to cefoxitin, but all were vancomycin susceptible. The oxacillin nonsusseptible ECN, detected by disk diffusion test were grown in agar screening oxacillin (6 μ g) supplemented with sodium chloride (4.0%) and submited to mecA detection by the PCR. Of the 32 nonsusseptible oxacillin CNS,, 93.7% developed in the oxacillin agar and the mecA gene was detected in 75.0%. This is the first report of mecA gene presence in CNS isolated from the saliva of healthy care workers. Attention must be given to CNS species identification, as well as the characterization of the nonsusceptible microorganisms, since healthy care workers may represent a reservoir of CNS